PENERAPAN PRINSIP-PRINSIP GOOD GOVERNANCE DALAM PELAYANAN PUBLIK DI KANTOR CAMAT SAIL KOTA PEKANBARU - nasution, sri roserdevi (Jurnal Niara, 2018)
Good Governance is the new face of hearts implement the principles of Public Service in the reform era. Public services Law No. 25 of 2009 is activities or circuit hearts Frame activities Fulfillment Services Under legislation with every citizen Share And Population differences Goods, services, and administrative services or Provided By Operation of Public Service. Public services carried out by the Government showed to society who asked service. Research Type singer is descriptive qualitative approach with, the techniques data collection using depth Interviews and Documentation. Results of Research Singer nearly all the principles of good governance hearts Services Not Running In accordance with From UNDP as Principles of Participation, legal rules, Transparency, Responsiveness, consensus-oriented, fairness, effectiveness, accountability, and strategic vision, Many Are Being inhibit the progress of the Principles of good governance. The conclusion from the findings of research, so authors concluded that the application of good governance in the hearts Implementation Services Head Office Sail Maximum yet. It is because that the singer Leadership And yet the implementation of communication subordinate ones in line so that although Head Already Trying to give the Best but if NOT in Support By subordinates will Difficult accomplished. Lack of human resources is a prayer One That Become an inhibiting factor hearts implementation of the Principles of good governance in the future Head Office Sail.